BUSINESS MODEL CANVAS DAN DIGITAL MARKETING GUNA MENINGKATKAN USAHA KULINER DI WISATA SUMBER BANTENG - Achmad Hamdan; Muhammad Aris Ichwanto; Agung Winarno; Suci Indah Permatasari; Adelia Nur Ramadhani (Politeknik Negeri Sriwijaya, 2023)
Digital technology-based marketing is also an opportunity for businesses to develop. Thus, there is a need for socialization regarding the Business Model Canvas (BMC) and Digital Marketing. The implementation methods are socialization activities, tutorials, discussions, field practices and evaluations. In culinary support at the Sumber Banteng Tourism location, this service activity involved 9 business people around the Sumber Banteng Tourism. The result of this dedication is that it can be seen that the participants have not maximized their business and social media for marketing their business. Through these results, it is very important to carry out assistance so that they can implement the material provided and innovate developments in information technology.